2006
DOI: 10.1007/bf02931589
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of minerals by 22 species of moderately halophilic bacteria in artificial marine salts media: Influence of salt concentration

Abstract: Precipitation of minerals was shown by 22 species of moderately halophilic bacteria in both solid and liquid artificial marine salts media at different concentration and different Mg2+-to-Ca2+ ratio. Precipitation of minerals was observed for all the bacteria used. When salt concentration increased, the quantity and the size of bioliths decreased, the time required for precipitation being increased. The precipitated minerals were calcite, magnesian calcite, aragonite, dolomite, monohydrocalcite, hydromagnesite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 26 publications
2
30
1
Order By: Relevance
“…The solution from which crystals were precipitated contained 50 mM Mg 2ϩ and 10 mM Ca 2ϩ (i.e. a 5:1 ratio), which would strongly favor precipitation of only aragonite (31,32). However, two strong bands at 1086.9 cm Ϫ1 (v1) and 1415 cm Ϫ1 (v3) in the NFIR spectrum, corresponding to calcite, were detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The solution from which crystals were precipitated contained 50 mM Mg 2ϩ and 10 mM Ca 2ϩ (i.e. a 5:1 ratio), which would strongly favor precipitation of only aragonite (31,32). However, two strong bands at 1086.9 cm Ϫ1 (v1) and 1415 cm Ϫ1 (v3) in the NFIR spectrum, corresponding to calcite, were detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Calcite (calcium carbonate) precipitation is a well-known example of extracellular bacterial biomineralization. Certain species of marine bacteria have been shown to precipitate minerals in water supplemented with artificial marine salt media and differing ratios of Mg 2ϩ to Ca 2ϩ concentrations (20). Several groups have investigated the geobiochemical significance of the presence of calcium carbonate in seafloor sediments in terms of calcite formation by marine bacteria (17).…”
mentioning
confidence: 99%
“…Numerous laboratory studies and observations in natural environments have demonstrated the bacterial precipitation of calcium carbonate (Rivadeneyra et al 1999(Rivadeneyra et al , 2000(Rivadeneyra et al , 2006bSánchez-Román et al 2007). One of the mechanisms of calcium carbonate precipitation most often proposed is that microorganisms produce NH 4 ?…”
Section: Resultsmentioning
confidence: 99%